Development and Evaluation of Avocado-based Functional Yogurt - Buddhika, Demanagammana P.R.N.; Anal, Anil Kumar; Datta, Avishek; Kuwornu, John K. M. (Pathum Thani : Asian Institute of Technology, 2018)
Avocado based functional yogurt was developed with better characteristics for the consumers, using avocado flesh and low-fat milk. Enzymatic browning of avocado flesh was reduced by using different anti-browning agents in order to obtain the better characteristics of yogurt. Three acids, citric acid (an acidulant), ascorbic acid (a reducing agent) and sorbic acid (an anti-microbial agent) probably used in food industry were used as anti-browning agents in this study. Avocado flesh samples were treated with ascorbic acid, citric acid and sorbic acid with their five different concentrations. Effectiveness of each anti-browning agent and its concentration were investigated by analyzing physical and chemical characteristics of formulated yogurt. Avocado yogurt that made with ascorbic acid treated flesh exhibited the least browning while yogurt made with sorbic acid treated flesh exhibited the highest browning. Preference for each avocado yogurt type treated with anti-browning agents was evaluated by sensory analysis. Better sensory properties were observed in yogurt made with citric acid treated avocado flesh. Citric scored highest for color, odor, flavor and overall quality while sorbic acid scored the highest for texture of yogurt. Avocado yogurt made with ascorbic acid treated flesh scored lowest in every sensory characteristic. When the concentration of anti- browning is increased, pH of the yogurt was decreased. With the decreasing pH, browning was expected to be limited and less L* (lightness) and ABI (Anti-browning Index) values were obtained. At the same time, pH of each type of yogurt was slightly increased during 10-days. Avocado yogurt made using 5% of ascorbic acid treated flesh showed the lowest pH. By using low fat milk for yogurt production, content of saturated fatty acids was expected to reduce and by using avocado, unsaturated fatty acid content was expected to increase in order to improve health benefits. And also, sugar was not added for a better health of consumer.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Biosystems Engineering
Capstone Project (B.Sc.)-Asian Institute of Technology, 2018
Keywords: Avocado; Yogurt; Functional food; Enzymatic browning